The Effect of the Guided Reading Model Assisted by the KWL (Know-Want to Know-Learned) Method on Reading Interests of Class V StudentsTO KNOW-LEARNED) Assisted Reading Model on Class Students’ Reading Interest - Nursinar Nursinar; Sulfasyah Sulfasyah; Munirah Munirah (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to determine the reading interest of fifth grade students through the application of the KWL (Know-Want To Know-Learned) Method Assisted Reading Model. This type of research is a quantitative study with a Quasi-Experimental Design. The research design used was Nonequivalent Control Group Design, in this study was given certain treatment (treatment), namely the control class and the experimental class.The sample in this study were students of class V in Cluster VII, Biringkanaya District, Makassar City, totaling 48 students. The data collection technique used was giving questionnaires. The data analysis technique used was descriptive statistics, inferential statistics, hypothesis testing T and manova.The results showed that the results of the fifth grade students' reading interest questionnaire in the experimental class used the KWL (Know-Want To Know-Learned) Assisted Reading Model. ) obtained an average value of r ata 83.09 which means the students' interest in reading is very good. So it can be concluded that there is an influence of the Guided Reading model assisted by the KWL (Know-Want To Know-Learned) method on the reading interest of Class V students throughout Cluster VII, Biringkanaya District, Makassar City